Financing the Zambia social cash transfer scale-up: A tax benefit microsimulation analysis based on MicroZAMOD - Remmy Kampamba; Luca Pellerano; Charles Banda; Obbie Musama (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper assesses the effects on poverty and inequality of the alternative targeting approaches that Zambia's Social Cash Transfer programme could take as its expansion continues during the period of the country's Seventh National Development Plan (2017-21). It further assesses the domestic financing needs associated with alternative approaches. The Zambian government introduced support based on giving actual cash through social cash transfers aimed at reducing poverty and vulnerability in a sustainable and cost-effective way. Using data from the 2015 Living Conditions Monitoring Survey, we simulate static effects of the alternative social cash transfer design options and their total cost using MicroZAMOD. In the absence of social cash transfers, nationwide extreme poverty would be 1.6 percentage points higher than otherwise. The results show that the combination of alternative options, particularly the inclusion of children and increased transfer financed from increased domestic taxes levels, yields higher impacts on poverty reduction.
Keywords: C35; I31; I38; 330; inequality; microsimulation; MicroZAMOD; poverty reduction; social protection; unconditional social cash transfer; Zambia